A cross sectional study on nutritional status and dental caries among rural preschool children of Sullia taluk, Karnataka - P. V., Dinesh; S. V., Bhargav; Kulkarni, Annarao Gunderao (International Journal Of Community Medicine And Public Health, 2017)
Background: A double burden of malnutrition in children, in the form of undernutrition and obesity exists in our world. Poverty and various other sociocultural factors act as important determinants of malnutrition. There exist varying prevalence rates in different places. Under nutrition has also a role in dental caries. The objective of this study was to find the prevalence of malnutrition and dental caries among children going to Anganwadi’s in rural Sullia taluk of Karnataka. Methods: Line listing of Anganwadi children was done and by random sampling method, 205 children were selected for study. Nutritional status was assessed by anthropometric measurements and dental examination done according to WHO standards. Results: The prevalence of underweight, wasting and stunting were 27%, 11% and 40% respectively. 49% of children studied had dental caries. Conclusions: According to the classification for assessing severity of malnutrition by prevalence ranges among children, the study area is classified as a high prevalence area for malnutrition according to WHO. Dental caries was present in 49.27% of the children.